Transformation Geometry Learning by Crossword Puzzle Model - Ryan Angga Pratama (Variabel, 2018)
This research objective is to describe the effectiveness learning by crossword puzzle model and students’ learning achievement. The research method used experimental research, by One-Shot Case Study design, in which there was a group given a treatment, then its result/achievement in Transformation Geometry and students’ response about that model was analysed. This research was conducted in the University of Balikpapan. The subject of this research was the 5th semester students of Mathematics Programme (Class A & B). With questionnaire analysis, the effectiveness learning by crossword puzzle model is , and mean of students’ learning achievement are  (Very Good) and  (Good). Hence, learning by crossword puzzle model can give a good learning achievement for students of Mathematics Programme in University of Balikpapan.